Use of platinum electrodes for the electrochemical detection of bacteria. - Wilkins, J R (1978)
Platinum electrodes with surface area ratios of four to one were used to detect and enumerate a variety of gram-positive and gram-negative organisms. Linear relationships were established between inoculum size and detection time. End points for platinum electrodes were similar to those obtained with a platinum-reference electrode combination. Shape of the overall response curves and length of detection times for gram-positive organisms were markedly different than those for the majority of gram-negative species. Platinum electrodes are better than the platinum-reference electrode combination because of cost, ease of handling, and clearer definition of the end point.